Coping with stress, psychological resilience and psychiatric symptoms in migraine patients - Emir, Burcu Sirlier; Yildiz, Sevler; Kilicaslan, Asli Kazgan; Dogan, Serpil; Kurt, Osman; Ugur, Kerim (Bayrakol Medical Publisher, 2023)
Aim: Migraine is a prevalent chronic disease with unknown etiopathogenesis that affects the quality of life. In the present study, we aimed to investigate anxiety, depression, coping with stress and psychological resilience of migraine patients. Material and Methods: The study was conducted with 40 patients and 40 healthy individuals. The study data were collected with a sociodemographic and clinical data form, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Psychological Resilience Scale for Adults (RSA), and Inventory of Coping Strategies (ICS). Results: It was determined that the RSA-structural resilience, RSA-social competence, BDI, BAI, ICS-optimism and ICS-social support scores of the patients were significantly higher when compared to the control group, RSA-self-perception, RSA-future perception, RSA-familial conformity, RSA-social resources, RSA-total and ICS-safe approach scores were significantly lower in the patient group when compared to the controls. There were positive correlations between the number of migraine attacks and RSA-future perception, RSA-familial conformity, RSA-social resources and RSA-total scores of the patients; There was a significant negative correlation between the number of migraine attacks and ICS-optimism scores. Discussion: The incidence of anxiety and depression was significantly higher and psychological resilience was significantly lower in the patients when compared to the control group. It could be suggested that patients could prefer ineffective coping strategies and their psychological resilience could be low. The determination of the psychiatric complications associated with migraine could alter treatment interventions, and thus, the prognosis.
Keywords: Migraine; Depression; Anxiety; Resilience; Coping with Stress